Guidelines for the use and interpretation of diagnostic methods in adult food allergy. Issue 1 (December 2015) - Macchia, Donatella; Melioli, Giovanni; Pravettoni, Valerio; Nucera, Eleonora; Piantanida, Marta; Caminati, Marco; Campochiaro, Corrado; Yacoub, Mona-Rita; Schiavino, Domenico; Paganelli, Roberto; Gioacchino, Mario
Abstract Food allergy has an increasing prevalence in the general population and in Italy concerns 8 % of people with allergies. The spectrum of its clinical manifestations ranges from mild symptoms up to potentially fatal anaphylactic shock. A number of patients can be diagnosed easily by the use of first- and second-level procedures (history, skin tests and allergen specific IgE). Patients with complex presentation, such as multiple sensitizations and pollen-food syndromes, frequently require a third-level approach including molecular diagnostics, which enables the design of a component-resolved sensitization profile for each patient. The use of such techniques involves specialists' and experts' skills on the issue to appropriately meet the diagnostic and therapeutic needs of patients. Particularly, educational programs for allergists on the use and interpretation of molecular diagnostics are needed.